Ecofeminism in Dialogue - Vakoch, Douglas A.; Mickey, Sam (Lexington Books, 2017)
There are countless ways of thinking, feeling, and acting like an ecofeminist. Ecofeminism includes a plurality of perspectives, thriving in dialogue between diverse theories and practices involving ecological and feminist matters of concern. Deepening the dialogue, the contributors in this anthology explore critical and complementary interactions between ecofeminism and other areas of inquiry, including ecocriticism, postcolonialism, geography, environmental law, religion, geoengineering, systems thinking, family therapy, and more. This volume aims to further the cultural and literary theories of ecofeminism by situating them in conversation with other interpretations and analyses of intersections between environment, gender, and culture. This anthology is a unique combination of contemporary, interdisciplinary, and global perspectives in dialogue with ecofeminism, supporting academic and activist efforts to resist oppression and domination and cultivate care and justice.